Two-Phase Optimization Method for Determining Distribution Center Locations and Distribution Routes (Case Study: X Ltd.) - Muhammad Rayhan Azzindani; Nabila Fajri Kusuma Ningrum; Mega Rizkah Sudiar; Anak Agung Ngurah Perwira Redi (IPTEK Journal of Proceedings Series, 2020)
One of the main keys to establishing a company’s facilities is to determine the best location with consideration of proximity to customers. After determining the location using the P-Center method, the company aims to maximize its profit by minimizing the distribution costs. It can be minimized by finding the shortest route. The best route determination method used in this study is the Capacitated Vehicle Routing Problem. The initial solution was obtained from data processing with the Nearest Neighborhood algorithm. The routes obtained from this method are optimal local results so that they can still be optimized to obtain the optimal global results. The results will be reprocessed with improvement heuristics method, namely Simple Local Search to get the most optimal results. From this data processing, it will produce an output in the form of the location of the best facility and route construction by producing the minimum total of distribution cost.